2019
DOI: 10.7759/cureus.4793
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Antibiotic Prophylaxis and Discharge Prescriptions in the General Surgery Department

Abstract: Introduction Although there are international guidelines for surgical antibiotic prophylaxis (SP), the use of inappropriate SP is still a common problem. Most studies investigated SP applications in clean and clean-contaminated cases. However, antibiotics in the discharge prescriptions of these cases have not been adequately investigated. In this study, we aimed to examine the antibiotics in SP applications and discharged prescriptions together and to find out the causes of inappropriate use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…Moreover, considering the recent increase in antibiotic resistant pathogens on surgical wards [9], the importance of preventing the inappropriate use of SP becomes even more urgent. In a study we conducted in our own clinic, we found that our SP usage was highly inappropriate, and that these incorrect SP applications had even been continued onto the patients' discharge prescriptions [10]. For this reason, we decided to introduce an antibiotic stewardship program (ASP) to our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, considering the recent increase in antibiotic resistant pathogens on surgical wards [9], the importance of preventing the inappropriate use of SP becomes even more urgent. In a study we conducted in our own clinic, we found that our SP usage was highly inappropriate, and that these incorrect SP applications had even been continued onto the patients' discharge prescriptions [10]. For this reason, we decided to introduce an antibiotic stewardship program (ASP) to our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In literature evaluating how various surgical groups utilize SP, quite different rates of total compliance have been reported. For example, while total compliance to SP was less than 1% in Iran [14] and Korea [15], it was measured as 8-39.3% [4,10,11,16] in our country and 83.3% in South Africa, after introducing ASP [17]. A study by Hulscher et al, shows this variation in rates of antibiotic usage in hospitals to be influenced by many factors, such as cultural and contextual aspects, sociocultural and socioeconomic factors, organizational policies, attitudes and knowledge of the physician as well as the personality of both patients and doctors [2].…”
Section: Discussionmentioning
confidence: 99%
“…Local ethics committee approval was received for this study (21/13-2017). The questionnaire used for our survey was prepared together with infection control committee experts and general surgeons and firstly given to general surgeons in a tertiary education and research hospital [4]. Between May 2018 and April 2019, the questionnaire was distributed using a variety of methods: via e-mail, by hand, and posted on the web pages of various regional and national surgical associations.…”
Section: A Cross-sectional Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several studies focused on antibiotic prescribing habits in conjunction with surgeries in different countries having been recently published [ 16 , 17 , 18 ], little is known regarding the factors associated with SAP compliance in elective minor surgery [ 19 , 20 , 21 ]. Consequently, it is imperative to acquire such information.…”
Section: Introductionmentioning
confidence: 99%